Assessment of the disposability of radioactive waste inventories for a range of nuclear fuel cycles: Inventory and evolution over time. (15th April 2021) - Dungan, K.; Gregg, R.W.H.; Morris, K.; Livens, F.R.; Butler, G.
Abstract: Nuclear power has been identified as a key low emissions energy source, as such an understanding of fueling and disposal requirements of different fuel cycles is essential. The effect of closing the nuclear fuel cycle on heat generating waste production has been examined by quantifying wastes and assessing thermal and radiotoxic inventories going to long-term disposal. Using fuel cycle modelling software ORION, five nuclear fuel cycles have been modelled to quantify mass, packaged volume, thermal output and composition of spent fuel and HLW, normalised to electricity generation. Evolution of decay heat and radiotoxicity over disposal time scales is presented. Compared to an open fuel cycle baseline, there is little benefit apparent in thermal or radiotoxic output, when implementing a thermal recycle, though the mass of waste going to disposal is significantly reduced. Over an order of magnitude reduction in radiotoxicity is achievable if a closed fuel cycle with interim storage is deployed, and packaged volume is halved. Advanced recycling of spent fuel both reduces waste volume per TWhe and allows a period of interim storage to dramatically reduce the thermal output of wastes and radiotoxic inventory going to a disposal facility. Highlights: Five stand-alone fuel cycles at different levels of technological maturity modelled. Closing the fuel cycle using reprocessing halves the mass of waste going to disposal. Recycling of minor actinides and plutonium lowers thermal and radiotoxic inventories. Utilising SFR + interim storage (<200 years) can reduce thermal output by up to 95%. Significant reductions in disposal footprint may be possible with advanced fuel cycles.